Firm Growth and Value Chain Configuration in an Enlarged EU: A study of UK clothing firms - Davies, Sally (2007)
This dissertation outlines the fact that UK based clothing firms are seeking more and more retailing opportunities in the regions of Central and Eastern Europe. The area has received much attention since 10 countries from the region received EU accession in May 2004. It is highlighted how EU growth is contributing to the process of globalisation and the idea of convergence aiding the growth of firms into new regions. However, it is shown that value chain transferability is not always as simple as simply replicating activities carried out in other countries and the comparative structure and configuration of the value chain can play a very significant role in the potential of global expansion Firms that are seeking competitive advantage based on their sourcing strategies, although not bringing such activities in-house, are seeking much closer relationships and agreement-types with their supply and manufacturing partners. It has been shown that firms seeking competitive advantage from activities forward in the value chain are seeking an even bigger consolidation of activities and are aiming to vertically integrate as many of these activities as possible. Backward vertical integration has been shown to rarely be a sustainable source of competitive advantage, as within the RBV, the sourcing and manufacturing of products is something incapable of being unique, rare, inimitable, and non-substitutable. The exception being if firms have a monopoly over that section of the value chainÃÂ¦accordingly they can execute a competitive advantage from the activity. Overall, it is argued that a sustainable competitive advantage can be achieved in the region via the establishment of closer relationships with different players in the value chain. This will lead to dynamic capabilities and prevent core rigidity. Subsequently firms are seeking to bring in-house activities essential for their competitive advantage (eg, brand management, flexible distribution) and keeping activities that are more context (low cost) and location bound (comparative advantage, sourcing of raw materials) outsourced. This can only be a source of stainable competitive advantage when the scope of the firm's operations warrants it; and there is an adequate structure in place to manage it.